First record of mawsoniid coelacanths (Actinistia, Sarcopterygii) from the marine Rhaetian (Upper Triassic) of Bonenburg, Germany. Issue 2 (4th March 2021) - Hartung, Josephina; Sander, P. Martin; Friedman, Matt; Wintrich, Tanja
ABSTRACT: Coelacanths are represented today by a single genus, Latimeria . They are known to be 'living fossils', because their evolutionary history dates back into the Devonian. Through the Upper Triassic, coelacanths are represented by two families, the Latimeriidae and Mawsoniidae. While latimeriids represent their marine lineage, mawsoniids were, until recently (Deesri et al., 2018), thought to be exclusively freshwater inhabitants. Through the Late Triassic, mawsoniids originated in freshwater environments of America, and only little is known about their evolution in Europe during this time period. Here we report on two morphotypes of mawsoniid basisphenoids from the marine Rhaetian (Upper Triassic) Bonenburg locality (Kreis Höxter, North Rhine-Westphalia, Germany) showing that (1) Late Triassic coelacanths from Germany can be assigned to the family level, specifically to Mawsoniidae, (2) mawsoniid coelacanths were already present in Europe in the Late Triassic, and (3) these inhabited marine environments at the end of the Triassic, supporting the affinities of habitat preference of previous finds from France (Deesri et al., 2018). The results strengthen the hypothesis an intermediate marine phase between the origin of Mawsoniidae in freshwater environments of nowadays North America during the Late Triassic and their final occurrence in continental deposits of Western Gondwana (Africa and South America) and nowadays Europe in the Late Cretaceous (Cavin et al., 2019).